A Premature Sense of Empathy and Responsibility. Issue 157 (25th March 2018) - Bustelo, María
Abstract: María Bustelo relates her family and cultural values to her approach to evaluating across different cultures. Being responsible and helping others take responsibility for their evaluations and through them has grown important to her. See the interview document here:http://onlinelibrary.wiley.com/wol1/doi/10.1002/ev.20307/suppinfo . Read only. This should not be used in any form without explicit permission from the author.